The Effect of CEOs' Financial Knowledge on Unsystematic Risk, Considering the Moderating Effect of Managerial Ability - Bahram Ghanizadeh; Mohsen Dastgir; Afsaneh Soroushyar (Iranian Journal of Accounting, Auditing & Finance)
With the emergence of economic globalization, expansion of business activities and more complex financial, administrative and operational structures, the need for firms to have CEOs with capable financial and managerial knowledge has multiplied more than in the past. Leading companies will require specialized human capital such as knowledge-based CEOs to bring maximum productivity, efficiency, and value creation to stakeholders through effective corporate governance, risk management, optimal organizational resources, and increased profitability. This study investigates the effect of CEO knowledge and management ability on non-systematic risk and the effect of management ability on the relationship between the CEO's financial knowledge and unsystematic risk. The statistical population of this study is the companies listed on the Tehran Stock Exchange and the statistical sample size includes 147 companies for the years 2011 to 2020, which have been selected by the systematic elimination method. Combined data and multivariate regression using the generalized least squares method have been used to test the research hypotheses. The results show that the financial knowledge of CEOs has a negative and significant effect on non-systematic risk. The effect of management ability on non-systematic risk is also negative and significant. Another result of the study indicates that management's ability as a moderating variable does not have a positive and significant effect on the relationship between the financial knowledge of CEOs and non-systematic risk.